2023
DOI: 10.3390/vaccines11071266
|View full text |Cite
|
Sign up to set email alerts
|

The Screening of the Protective Antigens of Aeromonas hydrophila Using the Reverse Vaccinology Approach: Potential Candidates for Subunit Vaccine Development

Abstract: The threat of bacterial septicemia caused by Aeromonas hydrophila infection to aquaculture growth can be prevented through vaccination, but differences among A. hydrophila strains may affect the effectiveness of non-conserved subunit vaccines or non-inactivated A. hydrophila vaccines, making the identification and development of conserved antigens crucial. In this study, a bioinformatics analysis of 4268 protein sequences encoded by the A. hydrophila J-1 strain whole genome was performed based on reverse vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…The prevalence of AMR genes in both stains identified, could be used for control strategies. Another study for example concluded the identification of two highly conserved proteins in Aeromonas species suggesting their potential selection as candidate antigens for developing of vaccines 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of AMR genes in both stains identified, could be used for control strategies. Another study for example concluded the identification of two highly conserved proteins in Aeromonas species suggesting their potential selection as candidate antigens for developing of vaccines 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies employing reverse vaccinology, in silico analysis, and bioinformatics to predict antigenic vaccine candidates have recognized outer membrane proteins as significant virulence factors. These proteins have been investigated as vaccine candidates in various bacterial species, such as Aeromonas hydrophila [22], Salmonella typhi [32], and Klebsiella pneumoniae [33], due to their capacity to elicit an effective immune response. Here, using host-cell-binding and pull-down assays, we identified four putative OMPs from F. necrophorum subspecies necrophorum (17 kDa, 24 kDa, 43 kDa, and 74 kDa) and one CSP (66.3 kDa), which may function as important adhesins to mediate host-cell attachment, based on results from our in vitro study.…”
Section: Discussionmentioning
confidence: 99%
“…A unique facet of this research involves modern bioinformatics and in silico investigations, which place greater emphasis on exploring OMPs and secretory elements. This emphasis highlights these components as promising candidates in identifying vaccine targets [21,22]. OMP-mediated adherence is often the first step in infection, and thus, inhibiting this essential interaction represents a possible infection-prevention strategy [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…It can also be used to develop new strategies for preventing and treating antmicrobial resistance and virulence ( Beceiro et al 2013 ) in Pseudomonas, Helicobacter, Campylobacter, Enterococcus, Klebsiella, Acinetobacter, Salmonella, Haemophilus, Bacillus, and Aeromonas infections. Research from several groups in the last ten years ( Martino et al, 2011 , Liang et al, 2022 , Zhang et al, 2023 ) backs up the idea that some genes found in other genera were unique to Aeromonas or even to certain strains of Aeromonas. This was the prime reason to explore the genus Aeromonas in the later part of the investigations.…”
Section: Discussionmentioning
confidence: 99%